Implementasi Model Pembelajaran Kooperatif Think Pair Share untuk Meningkatkan Hasil Belajar Siswa - aristiawan aristiawan; Laudry Bayu Andryansah (Universitas Islam Negeri Imam Bonjol Padang, 2023)
This study aims to improve the science learning outcomes of class IX students in through application of the Think Pair Share (TPS) cooperative learning model. This type of research is a type of Classroom Action Research (PTK) which is carried out in 2 cycles. Where each cycle consists of 3 meetings. The research was conducted in September - October 2022 with the research subjects being class IX students of SMP N 2 Jetis Ponorogo. Data collection techniques used in this study are test. The test are essay test with a total of 10 items. The data obtained was then analyzed descriptively to see an increase in student learning outcomes. Based on the analysis, it is known that student learning outcomes have increased. This is evidenced by an increase in the class average score which was initially only 60.2 in the initial conditions to 86.3 at the end of cycle 2. Based on these data it can be concluded that the science learning outcomes of class IX students of SMP N 2 Jetis Ponorogo can be improved through the application of the Think Pair Share cooperative learning model.